El consumo sanitario inapropiado y la trivialización de la medicina - Segura Benedicto, Andreu (Aten Primaria, 2013)
One of the main problems of our health care system is its excessive use. The most evident results of this misuse are the waste of resources and the iatrogenic consequences that are not justified by any expectations in health improvement. Among the possible causes of this inappropriate use, the trivialization of medical practice should be emphasized. This entails not only a loss of respect and consideration, but facilitates and even stimulates reckless use. Although patients and health care workers are both responsible for this recklessness, politicians and health care managers should be held responsible more so. Without a real emancipation allowing health care users and the population to control the factors that determine their health, it is unlikely that the inappropriate use of health resources and its associated iatrogenic consequences will be reduced.